MANAJEMEN ASET DALAM RANGKA OPTIMALISASI ASET TETAP (TANAH DAN BANGUNAN) PADA PEMERINTAH PROVINSI SUMATERA BARAT - , FADLI ILHAM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research about asset management in order to optimization of fixet asset land and building in West Sumatra Provincial Government, the aims of this research is to analyze the influence of inventory of assets, legal audit of assets, assets valuation, as well as monitoring and control of assets to optimization of fixed assets (land and buildings) in the West Sumatera Province Government. Based on analysis by using purposive sampling method the number of research samples was taken as much as 55 respondents. The result of calculation of the perception of respondents regarding the implementation stage of assets management in order to optimization of fixet asset land and building in West Sumatra Provincial Government had been in good condition. Based on the analysis result using Multiple Linear Regression test indicated that the inventory of assets, legal audit of assets, monitoring and control of assets, an individually are proven have a positive and significant influence toward optimization of fixed assets (land and buildings) that means consistent with the hypothesis, assets valuation has indicate a positive slope but an individually has not been proven to have significant influence on the optimization of fixed assets (land and buildings). While the analysis results together/simultaneously indicated that all four variables, namely the inventory of assets, legal audit of assets, assets valuation, as well as monitoring and control of assets, are proved to have significant and positive influence to optimization of fixed assets (land and buildings) in West Sumatra Provincial Government.